2018
DOI: 10.1186/s12962-018-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of health promotion interventions for older people: do applied economic studies meet the methodological challenges?

Abstract: BackgroundIn the light of demographic developments health promotion interventions for older people are gaining importance. In addition to methodological challenges arising from the economic evaluation of health promotion interventions in general, there are specific methodological problems for the particular target group of older people. There are especially four main methodological challenges that are discussed in the literature. They concern measurement and valuation of informal caregiving, accounting for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…1 ) [ 5 , 19 , 23 31 ] Excluded reviews are shown in Additional file 4 . Of the included reviews (Table 1 ), five addressed different preventive measures for older people [ 25 , 27 ] or children/adolescents [ 26 , 28 , 30 ], while the others targeted physical activity [ 23 ], implementation of DPHP [ 24 ], alcohol prevention [ 31 ], behavior change [ 5 ], injury prevention [ 29 ], or different areas of prevention [ 19 ]. Overall, these reviews included 494 economic analyses (CEA: 42%, CUA: 20%, different types of economic study: 16%, CCA: 15%, CBA: 6%, CMA: 1%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ) [ 5 , 19 , 23 31 ] Excluded reviews are shown in Additional file 4 . Of the included reviews (Table 1 ), five addressed different preventive measures for older people [ 25 , 27 ] or children/adolescents [ 26 , 28 , 30 ], while the others targeted physical activity [ 23 ], implementation of DPHP [ 24 ], alcohol prevention [ 31 ], behavior change [ 5 ], injury prevention [ 29 ], or different areas of prevention [ 19 ]. Overall, these reviews included 494 economic analyses (CEA: 42%, CUA: 20%, different types of economic study: 16%, CCA: 15%, CBA: 6%, CMA: 1%.…”
Section: Resultsmentioning
confidence: 99%
“…security: 57% - other: 18% Perspective : - societal: 84% - health sector: 8% - not stated: 8% n.a. Huter et al (2018) [ 25 ] a DPHP-interventions for older people n = 8 CEA = 25% CUA = 25% Different types = 50% TBA/MBA: n = 4/4 Time horizon all : - ≤ 2y: 75% - lifetime: 13% TBA : ≤ 2y 100% MBA : lifetime 25% Intermediate HO : all studies (e.g., falls, physical activity) HO/PbO : 88% (fall-related fractures, QALYs) Non-HO : 13% (social benefits such as ‘general self-efficacy’, ‘well-being’, or ‘loneliness’) Categories : − labor/soc. security: n.a.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Productivity loss was calculated based on an income loss of CAD 29.55/hour [28] over the time calculated for an average clinic visit [29], return travel time, and estimate of time for parking and finding the clinic (2.53 h). Productivity loss was only evaluated for patients <65 years old, comprising 23% of MDC patients (79/350) [30,31]. Given 371 fewer visits in MDC, this resulted in patient productivity loss reduction of CAD 6,379.…”
Section: Economic Analysismentioning
confidence: 99%